Global-Local Interface and the Anthropology of Nepal - Upadhyay, Prakash (Himalayan Journal of Sociology and Anthropology, 2011)
Globalization, altering role of WTO, expanding markets in Asia and Latin America, the emergence of prosperous middle class with heavy inluence of satellite television and the rise of consumerism has introduced a new transnational class structure. From a theoretical perspective, although deteriorisation is fundamental to understanding globalization, any piece of land can never be completely overcome without winning the heart and mind of the local people. In a context of global-local interface, deteriorisation must unavoidably be escorted by the process of relocalization of the cultures and rtaditions of backward world. DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4673 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 160-176